2022
DOI: 10.1007/s12144-022-03348-9
|View full text |Cite
|
Sign up to set email alerts
|

I Want More! The Role of Child, Family and Maternal Characteristics on Child Dispositional Greed and Sharing Behavior

Abstract: Greed is often regarded as a negative trait that impedes prosocial behavior in adults. Yet, relatively little is known about the development of greed and its effects on children. We examine the effect of dispositional greed on sharing behavior in 4-to-6-year-olds. In addition, we identified potential factors associated with child greed, including child, family, and maternal characteristics. This study with 63 mother–child dyads (Agechild = 5.11, SD = 0.88, 50.8% female) revealed that child greed was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…We propose that greedy individuals may maintain typical threat-related emotion processing supported by the amygdala but might show reduced vmPFC-related generation and regulation of negative emotions. This viewpoint is backed by numerous questionnaire studies reporting increased negative affect and psychopathology among greedy individuals [89,92,93,106]. Task-based PPI analyses showed that when processing negative emotion faces, greedy individuals in Cohort 1 tended to exhibit weaker functional connectivity between the vmPFC and the top-down control network/visual pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that greedy individuals may maintain typical threat-related emotion processing supported by the amygdala but might show reduced vmPFC-related generation and regulation of negative emotions. This viewpoint is backed by numerous questionnaire studies reporting increased negative affect and psychopathology among greedy individuals [89,92,93,106]. Task-based PPI analyses showed that when processing negative emotion faces, greedy individuals in Cohort 1 tended to exhibit weaker functional connectivity between the vmPFC and the top-down control network/visual pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we posit that greedy individuals might keep general and typical threat-related emotion processing subserved by the amygdala, including coding, discrimination, recognition, and automatic evaluation, but might exhibit decreased vmPFC-related generation and regulation functions responsible for negative emotions. Indeed, a large number of questionnaire studies support such viewpoint that more negative affect and negative psychopathology were observed in the greedy population (Van et al, 2022;Veselka et al, 2014;Vrabel et al, 2019;.When processing negative emotion faces, PPI analyses further showed that greedy individuals are prone to manifest weaker functional connectivity between the vmPFC and top-down control network/visual pathway in Cohort 1. Here, the top-down control network is composed of the prefrontal cortex (i.e., dlPFC) while the visual pathway consists of the MTG and LOC.…”
mentioning
confidence: 93%